Development of Feature Based Learning Media Instagram in Learning Writing Procedure Text at SMP Negeri 2 Imogiri Yogyakarta - Soleha, Isnani Marhatun; Jamilah, Fitri; Susetyo, Susetyo (UNIB Press, 2024)
The objectives of this research: (1) to determine the development of learning media based on Instagram features with the 4-D model (Define, Design, Develop, Disseminate) in learning procedural text writing skills for class VII junior high school students. (2) describe the feasibility of learning media based on Instagram features in learning text writing skills in class VII junior high school learning procedural texts. (3) describe the practicality of learning media based on Instagram features in learning procedural text writing skills in class VII junior high school. This research developed with 4D model and carried out at SMP Negeri 2 Imogiri in 2023/2024. The subjects of this research were students in class VII F with a sample of 15 students. The development procedure was carried out in four stages, namely define, design, develop, disseminate. Data collection techniques used student response questionnaires, media expert validation sheets, material expert validation sheets, pretest and posttest. The results of this research show: (1) the Instagram feature-based learning media developed for learning procedural text writing skills for class VII students at SMP Negeri 2 Imogiri has been carried out in accordance with the stages of the 4-D Model, namely Define, Design, Develop, Disseminate, (2) the process of developing learning media based on Instagram features is carried out in stages, namely (1) definition, (2) design, (3) development and (4) implementation. (2) Instagram feature-based learning media developed for learning procedure text writing skills for class VII students of SMP Negeri 2 Wonogiri with the 4-D model (Define, Design, Develop, Disseminate) is suitable as a learning media. The results of the assessment from experts on the media being developed obtained a score of 3.4, including in the good category, and the assessment from material experts was 3, including in the good category. (3) Instagram feature-based learning media developed for class VII students at SMP Negeri 2 Imogiri in learning procedural text writing skills using the 4-D model was declared practical for use in learning. the percentage of student learning completeness from 20% to 73.3% was declared valid.